ANALISIS BRAND SWITCHING PADA ONLINE MARKETPLACE SHOPEE OLEH GENERASI Z - Saras Miranda Putri (2021)
The emergence of various online marketplace brands has made customers make brand switching due to several factors. Using quantitative study with the purpose of identifying the effect of promotion, service quality, and variety seeking on brand switching. The population of this study are Shopee users and other online marketplaces born in the period 1995-2010 who live in the JABODETABEK area, with the total of 100 respondents as the used sample, and a non-probability sampling technique with purposive sampling as a sampling technique. Hypothesis testing uses the SPSS version 23 for Windows. The hypothesis in this study used a statistical method of multiple linear analysis with the t-test, f-test, and R2 test. This research shows that the promotion variable has an influence on brand switching with a T-test value of 2.146> 1.66, for service quality variables it has an influence on brand switching with a T-test value of 3.279> 1.661, and for the variety seeking variable there is also an influence on brand switching with T-test value 2.156> 1.661. The conclusion of this study is that it is important for marketers to pay attention to the variables of promotion, service quality, and variety seeking because they have the effect of making customers do brand switching.